A new species of pitviper of the genus Popeia (Squamata: Viperidae) from Pulau Tioman, Pahang, West Malaysia - Grismer, L. Lee; Grismer, Jesse L.; Mcguire, Jimmy A. (Zootaxa, 2006)
We describe a new species of pitviper Popeia buniana from Pulau Tioman, Pahang State, West Malaysia based on it having unique aspects of scalation, body proportions, and color pattern. Its long, thin body is in contrast with the shorter, more robust bodies of other arboreal pitvipers, suggesting it may be an active forager rather than an ambush feeder. Its close relationship to P. barati and P. sabahi of Sumatra and Borneo, respectively, rather than with species of the adjacent Malay Peninsula is in accord with biogeographic patterns of other flora and fauna endemic to the islands of the Outer Arc of the Seribuat Archipelago.